Two semen-thawing procedures compared by competitively mating beef cows - Odde, Kenneth G.; Kiracofe, G.H.; Ward, H.S.; Brethour, J. (Kansas State University. Agricultural Experiment Station, 2011)
Seventy-five cows were used to compare the fertilizing abilities of sperm packaged in 0.5-ml straws and thawed in warm water to similarly packaged sperm thawed in the inseminating gun. A system of competitive mating provided for inseminating each cow twice. After cows had estrus synchronized, each was artificially inseminated with one straw of Angus semen plus one straw of Simmental semen; semen in one straw was thawed in warm water, the other in the inseminating gun. Calves produced indicated the fertilizing sperm. Of the 20 cows that conceived at the synchronized estrus, 16 conceived to warm water-thawed semen and 4 to semen thawed in the gun. These data indicate that sperm thawed in warm water before breeding were more capable of fertilization when tested in the same cow against sperm thawed in the inseminating gun.
Keywords: Beef; Semen-thawing procedures